2021
DOI: 10.3390/ijms22031004
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Canstatin against Ventricular Arrhythmia Induced by Ischemia/Reperfusion Injury: A Pilot Study

Abstract: Ventricular arrhythmia induced by ischemia/reperfusion (I/R) injury is a clinical problem in reperfusion therapies for acute myocardial infarction. Ca2+ overload through reactive oxygen species (ROS) production is a major cause for I/R-induced arrhythmia. We previously demonstrated that canstatin, a C-terminal fragment of type IV collagen α2 chain, regulated Ca2+ handling in rat heart. In this study, we aimed to clarify the effects of canstatin on I/R-induced ventricular arrhythmia in rats. Male Wistar rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…We also found Anxa2 translocated to the membrane in microglial cells in response to OGD/R. Several studies have suggested that I/R and OGD/R exposure triggered the elevation of intracellular Ca 2+ concentration ( 43 , 99 ). While Anxa2 is a member of the family of Ca 2+ -dependent anionic phospholipid-binding proteins, Anxa2 can bind cell surface receptor S100a10, increasing the Ca 2+ sensitivity of Anxa2 and leading to binding membranes ( 100 ).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We also found Anxa2 translocated to the membrane in microglial cells in response to OGD/R. Several studies have suggested that I/R and OGD/R exposure triggered the elevation of intracellular Ca 2+ concentration ( 43 , 99 ). While Anxa2 is a member of the family of Ca 2+ -dependent anionic phospholipid-binding proteins, Anxa2 can bind cell surface receptor S100a10, increasing the Ca 2+ sensitivity of Anxa2 and leading to binding membranes ( 100 ).…”
Section: Discussionsupporting
confidence: 66%
“…The OGD/R model has been described previously ( 43 ). BV2 cells were plated in an anaerobic incubator with 5% CO 2 and 95% atmospheric air overnight.…”
Section: Methodsmentioning
confidence: 99%
“…NRCFs and NRCMs were isolated from neonatal Wistar rats as described previously [ 28 , 29 ]. The hearts were harvested from neonatal Wistar rats (1–3-day-old) and transferred immediately into the dish containing phosphate buffered saline (PBS) with 20 mM 2,3-butanedione monoxime (BDM) on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Arresten has been shown to reduce the invasiveness of squamous cell carcinoma in mice [ 177 ]. Canstatin has also been shown to prevent ventricular arrhythmia in an ischemia/reperfusion rat model, partly by inhibiting the production of reactive oxygen species and the elevation of intracellular Ca 2+ levels [ 178 ]. Additionally, canstatin also protected the rat right ventricle from fibrotic remodeling induced by experimental pulmonary arterial hypertension, possibly by interfering with Ca 2+ /calcineurin pathways [ 179 ].…”
Section: Targeting With Collagenmentioning
confidence: 99%